VERTICAL DISTRIBUTIONS OF TEMPERATURE, SALINITY AND GEOSTROPHIC FLOW ALONG 114°E IN THE SOUTHERN OCEAN IN OCTOBER 1970 (EXTENDED ABSTRACT) (Eleventh Symposium on Polar Biology) - ナガノブ, ミキオ; NAGANOBU, Mikio (National Institute of Polar Research, 1990)
P(論文) departmental bulletin paper